Climate-informed environmental inflows to revive a drying lake facing meteorological and anthropogenic droughts - Aneseh Alborzi; Ali Mirchi; Hamed Moftakhari; Iman Mallakpour; Sara Alian; Ali Nazemi; Elmira Hassanzadeh; Omid Mazdiyasni; Samaneh Ashraf; Kaveh Madani; Hamid Norouzi; Marzi Azarderakhsh; et al. (Environmental Research Letters, 2018)
The rapid shrinkage of Lake Urmia, one of the world’s largest saline lakes located in northwestern Iran, is a tragic wake-up call to revisit the principles of water resources management based on the socio-economic and environmental dimensions of sustainable development. The overarching goal of this paper is to set a framework for deriving dynamic, climate-informed environmental inflows for drying lakes considering both meteorological/climatic and anthropogenic conditions. We report on the compounding effects of meteorological drought and unsustainable water resource management that contributed to Lake Urmia’s contemporary environmental catastrophe. Using rich datasets of hydrologic attributes, water demands and withdrawals, as well as water management infrastructure (i.e. reservoir capacity and operating policies), we provide a quantitative assessment of the basin’s water resources, demonstrating that Lake Urmia reached a tipping point in the early 2000s. The lake level failed to rebound to its designated ecological threshold (1274 m above sea level) during a relatively normal hydro-period immediately after the drought of record (1998–2002). The collapse was caused by a marked overshoot of the basin’s hydrologic capacity due to growing anthropogenic drought in the face of extreme climatological stressors. We offer a dynamic environmental inflow plan for different climate conditions (dry, wet and near normal), combined with three representative water withdrawal scenarios. Assuming effective implementation of the proposed 40% reduction in the current water withdrawals, the required environmental inflows range from 2900 million cubic meters per year (mcm yr ^−1 ) during dry conditions to 5400 mcm yr ^−1 during wet periods with the average being 4100 mcm yr ^−1 . Finally, for different environmental inflow scenarios, we estimate the expected recovery time for re-establishing the ecological level of Lake Urmia.